Global Perspectives on Nonalcoholic Fatty Liver Disease and Nonalcoholic Steatohepatitis - YILMAZ, YUSUF (WILEY, 2019)
Over the past 2 decades, nonalcoholic fatty liver disease (NAFLD) has grown from a relatively unknown disease to the most common cause of chronic liver disease in the world. In fact, 25% of the world's population is currently thought to have NAFLD. Nonalcoholic steatohepatitis (NASH) is the subtype of NAFLD that can progress to cirrhosis, hepatocellular carcinoma (HCC), and death. NAFLD and NASH are not only found in adults-there is also a high prevalence of these diseases in children and adolescents. Because of the close association of NAFLD with type 2 diabetes (T2DM) and obesity, the latest models predict that the prevalence of NAFLD and NASH will increase, causing a tremendous clinical and economic burden and poor patient-reported outcomes. Nonetheless, there is no accurate noninvasive method to detect NASH, and treatment of this disease is limited to lifestyle modifications. To examine the state of NAFLD among different regions and understand the global trajectory of this disease, an international group of experts came together during the 2017 American Association for the Study of Liver Diseases Global NAFLD Forum. We provide a summary of this forum and an assessment of the current state of NAFLD and NASH worldwide.
Keywords: UNITED-STATES; MORTALITY; EPIDEMIOLOGY; ASSOCIATION; RISK